Effects of nanowire geometry on skyrmion dynamics - Fook, Hiu Tung (2015)
There is significant scientific interest in the creation of a skyrmion-based memory device due to high stability and storage density of such a device. However, current-driven skyrmions are deflected from the intended direction due to the presence of Magnus force. In this project, nanowire geometry effects on skyrmion dynamics are investigated in attempt to achieve more precise control over currrent-driven skyrmions. [3rd Award]